Receptive and Productive Skills of Senior High School Students in a Secondary School - Jeramie S. Awa-ao; Josephine B. Baguio (Archives of Current Research International, 2025)
This study aimed to determine the significant relationship between receptive skills and productive skills among senior high school students. Employing a correlational research design, the study surveyed 148 students from a secondary education institution in Mati District, Division of Mati City, using standardized questionnaires administered face-to-face. Data were analyzed using the mean, Pearson product-moment correlation, and multiple linear regression. Results revealed that students exhibited a moderate level of both receptive and productive skills, suggesting functional language ability with room for improvement in fluency and consistency. A significant positive relationship was found between receptive and productive skills. Further analysis showed that both reading and listening—domains of receptive skills, significantly influenced students’ productive abilities. It is recommended that educators implement targeted strategies to enhance these interconnected language competencies.